The potential for using different substrates in green roofs - Cakar, Handan; Akat Saracoglu, Ozlem; Akat, Hulya; Kilic, Cenk Ceyhun; Adanacioglu, Hakan (Journal of Environmental Engineering and Landscape Management, 2023)
This research was carried out in Izmir-Turkiye and investigated the potential of using three different substrates (cocopeat, loofah and perlite) in the design of green roofs with succulents (Crassula ovata) in aim to improve their performance. In this research, four different groups (G1: Soil-Cocopeat, G2: Soil-Loofah, G3: Soil-Perlite and G4: Soil) were created according to the plant growing media used in the planting layer. The researchers conducted measurements of the drained irrigation water’s EC (Electrical Conductivity) value, pH value and drainage amount, the plant growing media’s temperature and moisture, the plant’s height and leaf number, and the amount of subsidence in the planting layer. In line with the results obtained from the evaluations of the analyses, it is possible to say that perlite (G3) offers more advantages than its alternatives in terms of many variables. However, according to the conclusive results, it has been understood that the use of a single type of substrate as plant growing media would not be sufficient to encourage the maximum performance of green roofs. To ensure that, considering the advantages of each substrate group, it is proposed that their combined use would be more beneficial.